Application of a Reliable LC-MS/MS Method for Determination of Rizatriptan in Healthy Subject Samples: Demonstration of Assay Reproducibility by Incurred Sample Reanalysis. (10th December 2012) - Patel, Dinesh S.; Sharma, Naveen; Patel, Mukesh C.; Patel, Bhavin N.; Shrivastav, Pranav S.; Sanyal, Mallika
Abstract : A reliable, rapid, and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay has been proposed for the determination of rizatriptan in human plasma using sumatriptan as internal standard (IS). The analyte and IS were extracted from 300  μ L human plasma via liquid-liquid extraction and the chromatography was achieved on Hypurity C18 (50 mm × 4.6 mm, 5  μ m) column under isocratic conditions. Detection of rizatriptan and IS was done by tandem mass spectrometry, operating in positive ionization and multiple-reaction monitoring mode. The limit of detection and lower limit of quantitation of the method were 0.04 and 0.20 ng/mL, respectively, with a linear dynamic range of 0.20–60.0 ng/mL. The intrabatch and interbatch precision (% CV) was ≤8.4% while the mean extraction recovery was >78% across quality control levels. Bench top stability, freeze and thaw stability, processed sample stability, and long-term stability in plasma were evaluated at two quality control levels. It was successfully applied to a bioequivalence study of 10 mg rizatriptan orally disintegrating tablet formulation in 40 and 32 healthy Indian male subjects under fasting and fed conditions, respectively. The reproducibility in the measurement of study data was demonstrated by reanalysis of 254 incurred samples.